Pengaruh Ukuran Pemerintah Daerah dan Fiscal Stress Terhadap Alokasi Belanja Modal di Provinsi Lampung - Risa Novianti; Khairudin (Jurnal EMT KITA, 2023)
This study aims to examine the effects of two variables, namely regional government size and financial pressures, on the distribution of investment spending in the districts/cities of Lampung province over the three last year, specifically 2019-2021. The districts/cities of Lampung province became the study population with a total of 48 regions and to obtain representative results this study used saturation sampling method. The methods used in data analysis and discussion are quantitative methods, applying descriptive statistical analysis, panel data regression analysis and hypothesis testing. These methods provide a more detailed picture of the impact of local government size and budgetary constraints on the allocation of investment spending. The results of this study indicate that partly or simultaneously, the size of the regional government (UPD) has a significant positive effect on the allocation of investment spending in the districts/cities of Lampung province. However, this study did not find any significant effect of budgetary stress (FIST) on investment expenditure allocation. These results can provide valuable information and policy recommendations for decision-making at the local government level to promote more efficient allocation of investment spending.